The Bacterial Ecosystem of Mother’s Milk and Infant’s Mouth and Gut - Biagi, Elena; Quercia, Sara; Aceti, Arianna; Beghetti, Isadora; Rampelli, Simone; Turroni, Silvia; Faldella, Giacomo; Candela, Marco; Brigidi, Patrizia; Corvaglia, Luigi (Frontiers in Microbiology, 2017)
The progressive building of the infants’ gut microbiota is pivotal for educating their immune system. Human breast milk is among the first sources of microbes for the assembly of the infant’s microbiota, but research struggles to give a demonstration for the origin of bacteria in milk. Aiming at contributing to the knowledge on assembly of the mother’s milk and infant’s microbiome, here we characterized the oral, gut and milk ecosystems in a homogeneous cohort of 36 healthy mother-infants pairs, by 16S rRNA next-generation sequencing. A limited number of OTUs was shared among the three ecosystems, including not only OTUs assigned to the well-known immune-modulating Bifidobacterium genus, but also specific Streptococcus and Staphylococcus OTUs, which were dominant in the infant’s mouth ecosystem. The high conservation of these OTUs among the three ecosystems seems to call for a worth exploring ecological role through targeted and/or culture-dependent techniques. Notwithstanding the limitations of a 16S rRNA gene-based molecular characterization, we might hypothesize that the baby’s mouth, being the transition point for the milk to reach the intestine, could play a role in both the gut microbiota assembly, via deglutition, and mother’s milk duct colonization, during suction.